Problem Based Learning dan Culturally Responsive Teaching: Membangun Pemahaman Konsep Geometri melalui Anyaman Besek dan Aseupan - Santiaji, Nelis Alfany; Prabawati, Mega Nur (Papanda, 2026)
The common perception of mathematics as an abstract subject leads to low student interest in learning mathematics. To address this, the synergy of the Problem Based Learning (PBL) model and the Culturally Responsive Teaching (CRT) approach is proposed as a solution. This study aims to describe the implementation process of PBL with a CRT approach and analyze its impact on the understanding of geometric concepts. The cultural context used is the traditional Sundanese woven crafts ‘besek’ and ‘aseupan’. This research uses a descriptive qualitative approach with random sampling, taking 33 students of class IX A at Al Hasan Ciamis Integrated Junior High School. The research instruments employed are cultural-based worksheets (LKPD) on ‘besek’ and ‘aseupan’ and supporting observation instruments. The research techniques include unstructured interviews and direct participant observation, with analysis conducted through the stages of data reduction, data presentation, and conclusion drawing. The results show that the integration of PBL and CRT through the cultural context of ‘besek’ and ‘aseupan’ helps students more easily understand abstract geometric concepts. The learning process becomes more student-centered, enhancing direct engagement and appreciation for local culture